Downstream nuclear events in brassinosteroid signalling - Vert, G; Chory, J (Nature, 2006)
Brassinosteroids (BRs) are steroid hormones that control many aspects of plant growth and development. BRs bind to the plasma membrane receptor kinase BRI1, and act through a signalling pathway that involves a glycogen synthase kinase-3-like kinase (BIN2) and a serine/threonine phosphatase (BSU1). Previous models proposed that BIN2 negatively regulates BR signalling by controlling the stability and subcellular localization of the related transcription factors BES1 and BZR1 by phosphorylation, in a manner reminiscent of the canonical Wnt signalling pathway of metazoans. Here we present strong evidence for a different mode of regulation of BR signalling. We show that BES1 is localized constitutively to the nucleus, where its activity is modulated by nuclear-localized BIN2 kinase. BIN2-mediated phosphorylation of BES1 inhibits its DNA-binding activity on BR-responsive target promoters and its transcriptional activity through impaired multimerization. Our observations demonstrate that phosphorylation-dependent inhibition of DNA binding and trans-activation is the key primary mechanism of BES1 regulation.